State-dependent changes in peak alpha frequency during visual engagement in children with and without autism spectrum disorder - Sano, Masuhiko; Hirosawa, Tetsu; Soma, Daiki; Kameya, Masafumi; Yuasa, Keigo; Yasumoto, Mai; Osaka, Yoko; Yoshimura, Yuko; Shiota, Yuka; Tanaka, Sanae; Hasegawa, Chiaki; Kikuchi, Mitsuru (Frontiers in Psychiatry, 2025)
Peak alpha frequency (PAF) is a neurophysiological marker of cortical maturation and cognitive function. We aimed to examine PAF reactivity to a visually engaging eyes-open (EO) condition, during which children watched a muted preferred video, compared to a dark-room (DR) resting state without sound, in children with ASD and their TD peers. We analyzed magnetoencephalography data from 68 cortical sources in children aged 5–10 (ASD: n=22; TD: n=29), calculating PAF during a resting-state DR condition and an EO condition involving silent video viewing. Linear mixed-effects models were used to assess the effects of diagnosis, condition, and their interaction on PAF, controlling for age and sex. The results indicated a significant interaction between diagnosis and condition in the right temporal region, where TD children consistently showed a higher PAF in the EO condition relative to the DR condition, whereas children with ASD did not. Furthermore, in TD children, greater PAF reduction in the right temporal region correlated with lower social responsiveness scores, suggesting a link between PAF reactivity and social functioning. These findings suggest that atypical PAF modulation in response to sensory input may reflect altered neural mechanisms underlying social information processing in ASD. Understanding PAF reactivity patterns can inform the development of ASD biomarkers.